Metal−Organic Frameworks: Why Make Them Small?. Issue 1 (19th October 2021) - Wang, Jiemin; Imaz, Inhar; Maspoch, Daniel
Abstract : Recent studies have demonstrated that metal−organic frameworks (MOFs) can be miniaturized down to the submicroscale and even nanoscale to create small MOFs. Herein, the basic concepts and recent progresses concerning the core question of "MOFs, why make them small?" are briefly introduced from three perspectives: those of size, shape, and processability. Small sizes endow MOFs with large outer surface area/volume ratios, leading to important differences in their characteristics (e.g., outer surface energy, number of defects, etc.) relative to their bulk scale counterparts and thus, opening the door to size‐dependent properties such as flexibility or catalytic performance. Downsizing MOFs also enables shaping of them into unusual shapes. Among the most appealing morphologies are 2D nanosheets, whose structure can favor certain porosity‐related applications. The controlled miniaturization of MOF particles also favors their integration onto surfaces and into devices as well as their colloidal stability, which in turn translates to the ability to use readily processable MOF‐based liquids in countless processes, such as to drive the assembly of sophisticated meso‐ and macroscopic architectures, gels, monoliths, and porous liquids. It is believed that ongoing research to shrink MOFs via nanotechnology, as has been done with other classes of materials, will continue to yield novel MOF‐related materials that exhibit unprecedented structural and functional properties. Abstract : Herein, the basic concepts and recent progresses concerning the core question of "metal−organic frameworks (MOFS), why make them with dimensions down to the submicrometer and nanometer length scale?" are briefly introduced from three perspectives: those of size, shape, and processability.